Positive electrode material, lithium ion battery and electric equipment

By adopting a double-layer clad structure on the surface of the ternary material, including lithium supplement agents and carbon materials, the problem of excessive lithium ion consumption during the first charging and discharging of lithium ion batteries is solved, and efficient lithium ion replenishment and battery performance improvement is achieved.

CN119812232APending Publication Date: 2025-04-11BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410840639.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium-ion batteries, especially during the first charging and discharging, a solid electrolyte interface (SEI) film will be formed on the negative electrode surface, resulting in excessive consumption of lithium ions and reducing the first-time Coulomb efficiency and specific capacity of the battery.

Method used

A double-layer cladding structure is adopted that is coated on the surface of the ternary material, wherein the first cladding layer includes the lithium supplement Li2NiO2 or Li5FeO4, and the second cladding layer includes a carbon material. This structure provides the battery with additional lithium ions when the battery is charged and discharged for the first time, compensates for lithium ion consumption during the formation of the negative electrode SEI film, and improves conductivity and chemical stability through carbon coating.

Benefits of technology

It significantly improves the first Coulomb efficiency and specific capacity of lithium-ion batteries, enhances the safety and cycle life of the battery, and avoids the problem of lithium supplementation agent absorbing water and deterioration in the air.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812232A_ABST
    Figure CN119812232A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a lithium ion battery and electric equipment, the positive electrode material comprises a ternary material, a first coating layer and a second coating layer, the first coating layer and the second coating layer coat the surface of the ternary material, the first coating layer comprises a lithium supplement agent, the second coating layer comprises carbon, the first coating layer is located between the ternary material and the second coating layer, and the second coating layer is located between the ternary material and the second coating layer. And the lithium supplement agent comprises one or more of Li2NiO2 and Li5FeO4. The positive electrode material has relatively high specific capacity and good conductivity, and is not easy to absorb water and deteriorate in air.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a positive electrode material, a lithium-ion battery and an electrical device. Background Art

[0002] With the popularity of electronic devices such as electric vehicles and smart phones, higher and higher requirements are placed on the energy density, safety and cycle life of lithium-ion batteries. Among the positive electrode materials of lithium-ion batteries, ternary materials have attracted widespread attention due to their high energy density and excellent electrochemical properties. However, during the charge and discharge process of ternary materials, especially during the first charge and discharge, a solid electrolyte interface (SEI) film will form on the negative electrode surface. This process will consume a large amount of lithium ions, resulting in a decrease in the first coulombic efficiency and loss of specific capacity.

[0003] In order to solve these problems, researchers have explored various improvement methods. Among them, by adding lithium supplements as additives to the positive electrode materials, additional lithium ions can be provided to the battery to compensate for the lithium ions consumed when the negative electrode SEI film is formed. However, when the lithium supplement is mixed with the positive electrode material, the lithium supplement may not be evenly distributed on the surface of the positive electrode material, resulting in some lithium supplements failing to fully function, and some lithium supplements such as Li 2 NiO 2 , Li 5 FeO 4 It has poor conductivity and easily absorbs water and deteriorates in the air, which has limited improvement on electrochemical performance, which limits its application in batteries. Summary of the invention

[0004] Based on this, the present application provides a positive electrode material, a lithium-ion battery and an electrical device, wherein the positive electrode material comprises a ternary material and a first coating layer and a second coating layer coated on the surface of the ternary material, the first coating layer comprises a lithium supplement, the second coating layer comprises carbon, the first coating layer is located between the ternary material and the second coating layer, and the lithium supplement comprises Li 2 NiO 2 , Li 5 FeO 4 The positive electrode material has a high discharge specific capacity and good electrical conductivity, and is not easy to lose water and deteriorate in the air.

[0005] In one embodiment, the ternary material includes one or more of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0006] In one embodiment, the ternary material includes nickel cobalt manganese oxide, and the mass ratio of elements in the nickel cobalt manganese oxide is nickel: cobalt: manganese = (60-90): (5-15): (5-25).

[0007] In one embodiment, based on the total mass of the ternary material, the mass proportion of the lithium supplement agent is 0.5%-5%, preferably 1%-4%.

[0008] In one embodiment, based on the total mass of the ternary material, the mass proportion of the carbon material is 0.5%-10%, preferably 1%-5%.

[0009] In one embodiment, the D50 of the ternary material is 5-15 μm.

[0010] The positive electrode material provided in the first aspect of the present application is uniformly coated on the surface of the ternary material, and can provide additional lithium ions to the battery during the first charge and discharge process of the battery to compensate for the lithium ions consumed when the negative electrode SEI film is formed. At the same time, the conductivity of the positive electrode material is improved by carbon coating, and it is not easy to lose water and deteriorate in the air.

[0011] In a second aspect, the present application also provides a method for preparing a positive electrode material, comprising the following steps:

[0012] S1, mixing the ternary material and lithium ferrite and sintering them;

[0013] S2. Mixing the sintered product with a carbon source to obtain a positive electrode material.

[0014] In one embodiment, in steps S1 and S2, a high-speed mixer is used for mixing, the speed of the high-speed mixer is 1000-5000 rpm, and the mixing time is 1h-5h.

[0015] In one embodiment, in step S1, the sintering temperature is 300°C-600°C.

[0016] In one embodiment, the sintering process also includes crushing and screening.

[0017] In one embodiment, the carbon source includes one or more of Super-P, coconut shell carbon, porous carbon and activated carbon.

[0018] The method for preparing the positive electrode material provided in the second aspect of the present application has a simple process, low cost, high repeatability, short cycle, low energy consumption, saves production costs, is suitable for the needs of large-scale production and preparation, and has good application prospects in the field of lithium-ion batteries.

[0019] In a third aspect, the present application provides a lithium-ion battery, comprising the positive electrode material provided in the second aspect of the present application. The lithium-ion battery provided in the present application has high capacity and long life.

[0020] In a fourth aspect, the present application provides an electric device, which includes a lithium-ion battery. Specifically, the electric device can be an electric car, an electric motorcycle, an electric bicycle, a mobile power supply, an unmanned aerial vehicle, a mobile phone, a computer, a camera, an electric tool, a smart home or a wearable device. The lithium-ion battery has a high cycle capacity, which is conducive to improving the performance of the electric device. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description. The specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0022] Figure 1 A schematic cross-sectional view of a positive electrode material provided in one embodiment of the present application.

[0023] Reference numerals:

[0024] Ternary material-10, first coating layer-11, second coating layer-12. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0026] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0027] Some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0028] With the rapid expansion of the market for electronic devices such as electric vehicles and smartphones, the performance requirements of lithium-ion batteries, as their power core, are becoming increasingly stringent. Especially in terms of energy density, safety and cycle life, lithium-ion batteries face huge challenges. In the selection of positive electrode materials, ternary materials have become the star materials in the industry due to their high energy density and excellent electrochemical properties. However, despite the many advantages of ternary materials, they still face some key problems in practical applications.

[0029] During the charge and discharge cycle of lithium-ion batteries, especially during the first charge and discharge process, a solid electrolyte interface (SEI) film will form on the surface of the negative electrode. This process consumes a large amount of lithium ions, resulting in a decrease in the initial coulombic efficiency of the battery and a loss of specific capacity. In addition, the side reaction between the electrolyte and the positive electrode material is also one of the important factors affecting battery performance. These side reactions may not only lead to gas generation, affecting the safety of the battery, but also reduce the cycle life of the battery.

[0030] Based on this, the present application provides a positive electrode material, the positive electrode material includes a ternary material and a first coating layer and a second coating layer coated on the surface of the ternary material, the first coating layer includes a lithium supplement, the second coating layer includes carbon, the first coating layer is located between the ternary material and the second coating layer, and the lithium supplement includes Li 2 NiO 2 , Li 5 FeO 4 One or more of .

[0031] In this application, the lithium supplement agent is coated on the ternary material, which can provide additional lithium ions to the battery during the first charge and discharge process of the battery to compensate for the lithium ions consumed when the negative electrode SEI film is formed. This compensation method can more effectively improve the initial coulombic efficiency and specific capacity of the battery compared to blending, and the lithium supplement agent coating layer can be more evenly distributed on the surface of the ternary material, thereby providing more uniform lithium ion supplementation in the entire electrode, avoiding the problem of uneven local lithium ion concentration that may occur during blending. The lithium supplement agent coating layer can serve as a physical protective layer to prevent excessive contact between the electrolyte and the ternary material, reduce side reactions between the material and the electrolyte, inhibit gas production, and improve the safety of the battery.

[0032] In this application, the carbon material as a coating layer, in addition to having good electrical conductivity, can also isolate moisture in the air, prevent the ternary material and lithium supplement agent from absorbing water and deteriorating, improve the chemical stability of the material, and the lithium supplement agent will produce active oxygen after decomposition, which can improve the SEI film and thus reduce the impedance of the material. However, since the lithium supplement agent is very easy to absorb water and deteriorate in the air, a layer of carbon material is coated on the outermost layer of the material. The carbon material has good electrical conductivity, and after the outermost layer is coated, it can isolate the influence of water vapor in the air on the material and prevent the material from deteriorating. Moreover, when the material is charging and discharging, the dense carbon layer on the surface can act as a physical protective layer for the material to prevent excessive contact between the electrolyte and the material, reduce the side reactions between the material and the electrolyte, inhibit gas production, and improve the safety of the battery.

[0033] Furthermore, the lithium supplement includes Li 2 NiO 2 , Li 5 FeO 4One or more of the above. Lithium supplements replenish lithium ions by adding lithium to the battery, effectively offsetting the irreversible lithium loss, thereby significantly improving the total capacity and energy density of the battery. For example, Li 5 FeO 4 As an ideal pre-embedded lithium additive, its theoretical capacity is as high as 867mAh / g, which can significantly increase the capacity of the battery. 2 NiO 2 The decomposition potential of Li is about 3.7V. 5 FeO 4 The decomposition potential of Li is about 3.5V and 3.8V, and the discharge voltage of ternary materials is generally 4.3V. 5 FeO 4 Lithium can be decomposed and released first, and the released lithium ions can make up for the lithium ions consumed when the SEI film is formed at the negative electrode of the battery, thereby improving the initial coulombic efficiency and specific capacity of the material, and Li 5 FeO 4 After decomposition, active oxygen will be produced, which can improve the SEI film and thus reduce the impedance of the material.

[0034] In one embodiment, the ternary material includes one or more of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide. Compared with other positive electrode materials, such as lithium iron phosphate and lithium manganese oxide, lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA) have a higher discharge voltage (greater than 4.3V), which helps to improve the energy density of the battery.

[0035] In one embodiment, the ternary material includes nickel cobalt manganese oxide, and the mass ratio of the elements in the nickel cobalt manganese oxide is nickel: cobalt: manganese = (60-90): (5-15): (5-25). In the present application, the ternary material can be selected from one or more of NCM523, NCM622, NCM613, NCM712, and NCM811.

[0036] In one embodiment, based on the total mass of the ternary material, the mass proportion of the lithium supplement agent is 0.5%-5%, preferably 1%-4%. The amount of lithium supplement material added is crucial to improving battery performance. In this application, when the amount of lithium supplement material added is controlled within the range of 0.01%-4%, the performance is better. This amount of addition can promote the lithium supplement material to be evenly coated on the surface of the ternary positive electrode material, effectively replenish lithium ions, improve the initial charge and discharge efficiency of the battery, and reduce material impedance. At the same time, this amount of addition avoids material waste, improves material utilization, and helps stabilize the battery structure and prolong cycle life. Optionally, based on the total mass of the ternary material, the mass proportion of the lithium supplement agent can be 0.5%, 1%, 2%, 3%, 4%, or 5%. Preferably, when the mass proportion of the lithium supplement agent is within the range of 0.3%-2%, the effect of lithium supplement agent coating is best.

[0037] In one embodiment, based on the total mass of the ternary material, the mass proportion of the carbon material is 0.5%-10%, preferably 1%-5%. In the present application, after experiments and tests, it was found that the amount of carbon material added was controlled within the range of 1% to 10% of the mass percentage of the ternary material, which can generally obtain better battery performance. This amount of addition helps the carbon material to form a uniform and effective coating layer on the surface of the ternary positive electrode material, which not only improves the conductivity of the material, but also reduces the hygroscopicity of the material to a certain extent, which may help to improve the energy density, cycle stability and service life of the battery. Optionally, based on the total mass of the ternary material, the mass proportion of the carbon material can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. Preferably, when the mass proportion of the carbon material is in the range of 1%-5%, the carbon coating effect is best.

[0038] In one embodiment, the ternary material is a ternary polycrystalline material. The polycrystalline material is a secondary particle, which is usually larger in size than the lithium supplement and has a better coating effect.

[0039] In one embodiment, the D50 of the ternary material is 5-15μm. When the D50 of the ternary material is in the range of 5-15μm, the difference in D50 between the positive electrode material particles and the coating material is moderate, which is conducive to the formation of a uniform and complete coating layer. Not only can the coating efficiency be improved, but also the quality of the coating layer can be ensured, thereby enhancing the electrochemical properties of the positive electrode material, such as the lithium supplement effect. At the same time, it can shorten the diffusion path of lithium ions in the positive electrode material, increase the migration rate of lithium ions, and enable the battery to maintain a high energy density during rapid charging and discharging. Optionally, the D50 of the ternary material can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.

[0040] The present application also provides a method for preparing a positive electrode material, comprising the following steps:

[0041] S1, mixing the ternary material and lithium ferrite and sintering them;

[0042] S2. Mixing the sintered product with a carbon source to obtain a positive electrode material.

[0043] The method in this application combines the two steps of sintering and mixing, simplifies the preparation process of positive electrode materials, and improves production efficiency. At the same time, by controlling the conditions of sintering and mixing, the structure and performance of positive electrode materials can be precisely controlled. Compared with traditional methods for preparing positive electrode materials, this method has higher flexibility and scalability, and is suitable for the combination of different types of ternary materials and carbon sources.

[0044] In one embodiment, in steps S1 and S2, a high-speed mixer is used for mixing, and the speed of the high-speed mixer is 1000-5000rpm, and the mixing time is 1h-5h. In the present application, the carbon coating method is high-speed mixing coating, and the high-speed mixer has a paddle at the bottom and a stirring rod above the top and bottom that rotates simultaneously to make the materials evenly mixed. This mixing method ensures the uniform mixing of the ternary material and lithium ferrite (in S1) and the sintered product and the carbon source (in S2). The appropriate speed (1000-5000rpm) and mixing time (1h-5h) not only improve the mixing efficiency, but also help to achieve the uniform coating of the lithium supplement material on the surface of the ternary polycrystalline positive electrode material, thereby improving the conductivity and stability of the material. At the same time, it also avoids the destruction of the material crystal structure caused by excessively high speed or excessively long mixing time, and ensures the electrochemical performance of the final product. Therefore, by accurately controlling the speed and mixing time of the high-speed mixer, we have achieved efficient, economical and controllable preparation of the positive electrode material.

[0045] In one embodiment, in step S1, the sintering temperature is 300°C-600°C. In the present application, the sintering temperature is controlled within the range of 300°C-600°C, which promotes the lithium supplement material to be evenly and effectively coated on the surface of the ternary material, thereby improving the conductivity and stability of the material. At the same time, the appropriate sintering temperature avoids the regrowth of the ternary polycrystalline material, maintains the advantages of its polycrystalline structure, and further ensures the high performance of the positive electrode material. Therefore, by precisely controlling the sintering temperature, we have successfully prepared a positive electrode material with excellent performance.

[0046] In one embodiment, the sintering process further includes crushing and screening. The crushing process reduces the size of the material particles, thereby improving the efficiency of subsequent processing and the active surface area of ​​the material, which is beneficial to optimizing the electrochemical performance. The screening process ensures that the particle size distribution of the positive electrode material particles is uniform, improves the uniformity and stability of the material, and meets the requirements of different applications. In one embodiment of the present application, a 200 mesh sieve is used for screening.

[0047] In one embodiment, the carbon source includes one or more of Super-P, coconut shell carbon, porous carbon and activated carbon. Super-P, coconut shell carbon, porous carbon and activated carbon are used as carbon sources for positive electrode materials, and they all have good electrical conductivity and can effectively improve the electronic conductivity of positive electrode materials. These carbon source materials also generally have a large specific surface area and / or porous structure, which is conducive to providing more active sites and increasing the reaction interface for lithium ion insertion / deinsertion, thereby enhancing the electrochemical properties of positive electrode materials. In addition, they also have a certain adsorption capacity, which helps to stabilize the electrode structure and inhibit the dissolution and loss of active substances. In one embodiment of the present application, Super-P with the best conductivity is preferably used as the carbon source to further improve the electrical conductivity of the material.

[0048] The positive electrode material preparation method provided in the present application has a simple process, uses a low-cost carbon source, has high repeatability, a short cycle, low energy consumption, saves production costs, is suitable for large-scale production needs, and has good application prospects in the field of lithium-ion batteries.

[0049] The present application provides a lithium-ion battery, comprising the positive electrode material provided in the first aspect of the present application. The lithium-ion battery provided in the present application has a low impedance of the lithium supplementation layer and a high cycle capacity.

[0050] The present application provides an electrical device, which includes a lithium-ion battery. The lithium-ion battery has a high capacity and is beneficial to improving the performance of the electrical device.

[0051] The technical solution of the present application is further illustrated below through specific embodiments and comparative examples.

[0052] Example 1

[0053] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 10 g (0.5%) Li 5 FeO 4 After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, the material was crushed by a roller, and then crushed through a 200-mesh sieve to obtain a sample recorded as F1. Then 50g (2.5%) Super-P was weighed and mixed with F1 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 9.89μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The positive electrode material: acetylene black: PVDF: = 100:3:3: was mixed evenly and coated on aluminum foil, then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0054] Example 2

[0055] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 20g (1%) Li 5 FeO 4After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, the material was crushed by a roller, and then crushed through a 200-mesh sieve to obtain a sample recorded as F2. Then 50g (2.5%) Super-P was weighed and mixed with F2 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 10.46μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The mixture was uniformly mixed according to the mass ratio of positive electrode material: acetylene black: PVDF: = 100:3:3: and then coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0056] Example 3

[0057] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 40g (2%) Li 5 FeO 4 After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking out, the material was crushed by a pair of rollers, and then crushed through a 200-mesh sieve to obtain a sample recorded as F3. Then 50g (2.5%) Super-P was weighed and mixed with F3 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 12.11μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The mixture was uniformly mixed according to the mass ratio of positive electrode material: acetylene black: PVDF: = 100:3:3: and then coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0058] Example 4

[0059] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 80g (4%) Li 5 FeO 4After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking out, the material was crushed by a pair of rollers, and then crushed through a 200-mesh sieve to obtain a sample recorded as F4. Then 50g (2.5%) Super-P was weighed and mixed with F4 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 14.52μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The positive electrode material: acetylene black: PVDF: = 100:3:3: was mixed evenly and coated on aluminum foil, then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to form a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0060] Example 5

[0061] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 100g (5%) Li 5 FeO 4 After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, the material was crushed by a pair of rollers, and then crushed through a 200-mesh sieve to obtain a sample recorded as F5. Then 50g (2.5%) Super-P was weighed and mixed with F5 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 16.95μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The mixture was uniformly mixed according to the mass ratio of positive electrode material: acetylene black: PVDF: = 100:3:3: and then coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0062] Example 6

[0063] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 40g (2%) Li 5 FeO 4After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking out, the material was crushed by a pair of rollers, and then crushed through a 200-mesh sieve to obtain a sample recorded as F6. Then 20g (1%) Super-P was weighed and mixed with F6 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 11.15μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The mixture was uniformly mixed according to the mass ratio of positive electrode material: acetylene black: PVDF: = 100:3:3: and then coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0064] Example 7

[0065] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 40g (2%) Li 5 FeO 4 After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, the material was crushed by a pair of rollers, and then crushed through a 200-mesh sieve to obtain a sample recorded as F7. Then 100g (5%) Super-P was weighed and mixed with F7 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 13.63μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The mixture was uniformly mixed according to the mass ratio of positive electrode material: acetylene black: PVDF: = 100:3:3: and then coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0066] Example 8

[0067] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 40g (2%) Li 5 FeO 4After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, the material was crushed by a roller, and then crushed through a 200-mesh sieve to obtain a sample recorded as F8. Then 200g (10%) Super-P was weighed and mixed with F8 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 15.1μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The mixture was uniformly mixed according to the mass ratio of positive electrode material: acetylene black: PVDF: = 100:3:3: and then coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0068] Example 9

[0069] Weigh 2.0 kg of ternary material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), 40g (2%) Li 5 FeO 4 After mixing in a high-speed mixer for 2 hours at a speed of 2500rpm, the material was placed in a box furnace and heated to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, the material was crushed by a pair of rollers, and then crushed through a 200-mesh sieve to obtain a sample recorded as F9. Then 50g (2.5%) Super-P was weighed and mixed with F9 in a high-speed mixer for 2 hours at a speed of 4000rpm. Then the sample was taken out and the D50 was measured to be 12.11μm. Acetylene black was used as a conductive agent and polyvinylidene fluoride (PVDF) was used as a binder. The positive electrode material: acetylene black: PVDF: = 100:3:3: was mixed evenly and coated on aluminum foil, then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet was used as a negative electrode to prepare a half-battery.

[0070] Comparative Example 1

[0071] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 40g (2%) Li 5 FeO 4Mix in a high-speed mixer for 2 hours at a speed of 2500rpm, and then place the material in a box furnace and heat it to 500℃ at a heating rate of 5℃ / m for 8 hours. After taking it out, crush the material with a roller, and then crush it through a 200-mesh sieve to obtain a sample recorded as D1. The particle size D50 of the sample is measured to be 11.21μm. Acetylene black is used as a conductive agent and polyvinylidene fluoride (PVDF) is used as a binder. The positive electrode material: acetylene black: PVDF: = 100:3:3: is mixed evenly and coated on aluminum foil, and then placed in a 120℃ oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; lithium sheet is used as a negative electrode to prepare a half-battery.

[0072] Comparative Example 2

[0073] The battery sample NCM was prepared according to the method in Experiment 1, except that the battery material used was the traditional (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), D50 is 8.84 μm, without lithium supplement coating and carbon coating.

[0074] Comparative Example 3

[0075] Weigh 2.0 kg of ternary material (LiNi 0.65 Co 0.15 Mn 0.2 O 2 ), 40g (2%) Li 5 FeO 4 After uniform mixing, the sample is recorded as D3. Acetylene black is used as a conductive agent and polyvinylidene fluoride (PVDF) is used as a binder. The positive electrode material: acetylene black: PVDF: = 100:3:3: is mixed uniformly and coated on aluminum foil, and then placed in a 120°C oven for vacuum drying for 24 hours, and then pressed and rolled to make a positive electrode sheet; the lithium sheet is used as the negative electrode to prepare a half-cell.

[0076] Test method:

[0077] (1) Charge and discharge cycle test

[0078] Take the prepared lithium-ion battery and charge it to 4.3V at a constant current of 1C at room temperature (25±3℃), then charge it to 0.05C at a constant voltage at 4.3V, leave it for 5 minutes, and then discharge it to 2.5V at a constant current of 0.5C, and leave it for 5 minutes. This is one cycle. Record the capacity retention rate after 1000 cycles. The cycle uses a NEWARE test cabinet (model CTE-4080D-5V30A). To ensure that the battery temperature is constant during the cycle test, the battery is placed in a high and low temperature test box (model CH1000T).

[0079] (2) Particle size test

[0080] According to Appendix A of GB / T 24533-2019, the particle size D50 of the material was tested using a Malvern laser particle size analyzer.

[0081] (3) DCIR test

[0082] Different batteries were loaded into the charge and discharge tester, charged at 0.2C current to 3.8V at 25℃ and left to stand for 10 minutes, discharged at 0.2C for 150min (50% SOC), left to stand for 2 hours, discharged at 1.5C for 30s, took points (20-30) and left to stand for 2h, and discharged at 1.5C constant current to 2.5V.

[0083] Table 1 Charge and discharge test

[0084] Charge specific capacity (mAh / g) Discharge specific capacity (mAh / g) Example 1 217.79 190.77 Example 2 225.13 200.78 Example 3 219.21 194.1 Example 4 221.43 199.46 Example 5 215.46 190.37 Example 6 214.75 197.54 Example 7 218.49 192.76 Example 8 215.46 189.16 Example 9 219.21 194.1 Comparative Example 1 214.26 188.03 Comparative Example 2 213.62 186.67 Comparative Example 3 210.21 185.49

[0085] Table 2 DCIR test

[0086] DCIR(Ω) Example 1 14.54 Example 2 11.79 Example 3 13.69 Example 4 15.76 Example 5 15.98 Example 6 12.35 Example 7 15.43 Example 8 15.91 Example 9 13.69 Comparative Example 1 16.79 Comparative Example 2 17.68 Comparative Example 3 18.13

[0087] The test results of Examples 1-9 and Comparative Examples 1-3 show that the discharge capacity of Examples 1-9 is relatively high. This is because the material has been double-coated and modified. During the charge and discharge process of the material, the lithium supplement agent in the inner coating layer of the material can release lithium ions to increase the gram capacity, and the outermost carbon coating can improve the conductivity of the material and reduce the polarization impedance of the inner coating layer so that the lithium supplement material in the inner coating layer can be better decomposed, and provide a good water isolation protection for the lithium supplement agent, so that the lithium supplement material will not deteriorate, and improve the utilization rate of the lithium supplement agent. Further, when the coating amount of the lithium supplement agent and the carbon layer further meets the preferred range of the present application, the conductivity and discharge capacity of the lithium ion battery improved by the present application are better.

[0088] The above are preferred embodiments of the present application, but they should not be construed as limiting the scope of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A positive electrode material, characterized in that: It includes a ternary material and a first coating layer and a second coating layer coated on the surface of the ternary material, the first coating layer includes a lithium supplement agent, the second coating layer includes carbon, the first coating layer is located between the ternary material and the second coating layer, and the lithium supplement agent includes one or more of Li2NiO2 and Li5FeO4.

2. The positive electrode material according to claim 1, characterized in that The ternary material includes one or more of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

3. The positive electrode material according to claim 1, characterized in that The ternary material includes nickel-cobalt-manganese lithium oxide, and the mass ratio of elements in the nickel-cobalt-manganese lithium oxide is nickel:cobalt:manganese=(60-90):(5-15):(5-25).

4. The positive electrode material according to any one of claims 1 to 3, characterized in that Based on the total mass of the ternary material, the mass proportion of the lithium supplement is 0.5%-5%, preferably 1%-4%.

5. The positive electrode material according to any one of claims 1 to 3, characterized in that Based on the total mass of the ternary material, the mass proportion of the carbon material is 0.5%-10%, preferably 1%-5%.

6. The positive electrode material according to any one of claims 1 to 3, characterized in that The D50 of the ternary material is 5-15 μm.

7. A method for preparing a positive electrode material, characterized in that: The following steps are involved: S1, mixing the ternary material and the lithium supplement agent and sintering them; S2. Mixing the sintered product with a carbon source to obtain a positive electrode material.

8. The method for preparing the positive electrode material according to claim 7, characterized in that: In steps S1 and S2, the mixing is performed using a high-speed mixer, the speed of the high-speed mixer is 1000-5000 rpm, and the mixing time is 1 h-5 h.

9. The method for preparing the positive electrode material according to claim 7, characterized in that: In step S1, the sintering temperature is 300°C-600°C.

10. The method for preparing the positive electrode material according to claim 7, characterized in that: In step S1, the sintering process also includes crushing and screening.

11. The method for preparing the positive electrode material according to claim 7, characterized in that: In step S2, the carbon source includes one or more of Super-P, coconut shell carbon, porous carbon and activated carbon.

12. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the preparation method according to any one of claims 7 to 11.

13. An electrical equipment, characterized in that: The electrical equipment comprises the positive electrode material according to any one of claims 1 to 6 or the lithium ion battery according to claim 12.